(untitled) (Research, Society and Development, 2023)
With the arrival of the climacteric and menopause, different manifestations arise and, despite being much discussed subjects, they are still a taboo in society, as a result, many women are unaware of the signs, symptoms and ways to improve their health. Therefore, the present work aimed to describe the scientific evidence about the challenges in the nurse’s performance in the face of climacteric and menopause in Primary Health Care. This is a bibliographic, descriptive study, of the integrative review type of scientific literature, through a systematic search in the LILACS, BDENF and EBSCO databases, during September 2022. 9 articles were selected that showed the actions carried out by the nurses directed to climacteric and menopause, women’s knowledge and perceptions about these periods and different gaps in assistance to the demands of these transitions within the scope of PHC. In view of the evidence, the role of the nurse ranges from qualified reception, also acting as an educator in this process. And, based on the identified gaps, the theme must be worked on from graduation to specific training, in addition to the need for changes in public policies in order to encourage actions that seek to qualify the assistance to women in the climacteric and menopause.